Back Cover: Manipulating Intermetallic Charge Transfer for Switchable External Stimulus‐Enhanced Water Oxidation Electrocatalysis (Angew. Chem. Int. Ed. 44/2023) - Chalil Oglou, Ramadan; Ulusoy Ghobadi, Turkan Gamze; Hegner, Franziska Simone; Galán‐Mascarós, José Ramón; López, Núria; Ozbay, Ekmel; Karadas, Ferdi (Angewandte Chemie International Edition, 2023)
Applying external stimuli is critical to circumvent the limitations imposed by linear scaling relationships in electrocatalytic applications. Franziska Simone Hegner, Ferdi Karadas et al. demonstrate in their Research Article (e202308647) that the water oxidation electrocatalytic activity of Co–Fe Prussian blue could be enhanced under magnetic field and light irradiation, which originates from an external‐stimulus sensitive spin‐crossover process. Cover art design: Asya Kübra Özvural @asyaknos.